Psychological capital and death anxiety in pancreatic cancer patients: a latent profile analysis - Yang, Dajun; She, Tianyu; Gui, Gui; Li, Linwei; Zhou, Zhiwen; Liu, Lu; Liu, Nian (Frontiers in Psychiatry, 2025)
Prior research has predominantly adopted variable-centered approaches to demonstrate significant correlations between psychological capital and death anxiety. However, few studies have investigated the heterogeneity of these constructs among patients with pancreatic cancer. To address this gap, we employed a random sampling method to recruit 513 patients with pancreatic cancer. Latent profile analysis was conducted to examine their psychological capital and death anxiety profiles, followed by univariate analysis and multinomial logistic regression to identify influencing factors. The results revealed three distinct profiles: high psychological capital–low death anxiety, moderate psychological capital–moderate death anxiety, and low psychological capital–high death anxiety. Key determinants included Gender, age, place of residence, and cancer stage. These findings enhance our understanding of the psychological recovery trajectory in pancreatic cancer patients, enabling clinicians to develop targeted interventions based on distinct psychological profiles to improve mental health outcomes.